Unmet Need for Community Based Physiotherapy in Canada - Wojkowski, Sarah (My University, 2018)
This thesis includes four manuscripts with overarching objectives to identify if Canadians experience unmet need for physiotherapy. McIntyre et al.’s framework was utilized across the manuscripts to explore reasons why unmet need may exist. The first manuscript presents a scoping review investigating unmet need for physiotherapy across Canada. The objective was to describe current evidence for unmet need for community-based physiotherapy services (CBPTS). Adults with chronic conditions versus those without, or who lived in rural versus urban communities were more likely to report unmet need for CBPTS. Availability and affordability were identified as reasons for unmet need. The second manuscript presents a secondary data analysis of three Canadian Community Health Survey (CCHS) cycles (2001, 2003, 2005) for three provinces: Ontario (ON), Alberta (AB), British Columbia (BC). This study investigated factors that explain variations in self-reported unmet needs of individuals with specific chronic conditions. Unmet need for treatment of a physical health problem (PHP) was the most common type of need in all three cycles. Affordability was the only domain with significant differences between cycles in two provinces. Women were less likely than men, and older persons less likely than persons 40 – 45 years, to report unmet need for treatment of a PHP. The third manuscript analyzed CCHS data for ON, AB and BC to investigate which socio-demographic variables were associated with reporting a visit to a physiotherapist in three cycles. People with lower income were less likely to report a physiotherapy visit compared to people with higher income. Women, and individuals with an injury or physical activity limitation were more likely to report a physiotherapy visit. The fourth manuscript presents themes from key informant interviews that explored the partial removal of physiotherapy from the Ontario Health Insurance Plan (“delisting”). Partial delisting contributed to increased unmet need immediately following, and more than ten years post implementation. Longstanding unmet need due to affordability and availability was identified.
Keywords: unmet need, physiotherapy